1980
DOI: 10.1159/000241258
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of Renal Sodium Handling in Newborn Infants

Abstract: In an attempt to delineate the specific tubular defect in sodium reabsorption in low-birth-weight neonates, fractional sodium excretion (CNa/Ccr), distal tubular sodium delivery (CNa+CH2O), and distal tubular sodium reabsorption [(CH2O/CH2O+CNa) × 100] were determined in 8 healthy premature and 10 full-term newborn infants. The mean birth weight was 1,701 g (range: 1,240–2,120 g) and the mean gestational age was 32.6 weeks (range: 28–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 22 publications
1
14
0
1
Order By: Relevance
“…It is generally accepted that the kidney is immature at birth as expressed by the low glomerular filtration rate [12,13], by the limited capacity to reabsorb the ultrafiltered sodium [14][15][16] and by the reduced ability to concentrate urine [17], The maturation pat tern is dependent on the gestational age as evidenced by the more limited capacity of the kidney observed in preterm infants when compared with fullterm infants. Our data are consistent with previous reports by other au thors who studied the renal function in pre term and fullterm infants at similar period of life [3,17,18], Regarding kallikrein excretion, when comparing the preterm with the fullterm newborn groups, the preterm newborns had lower kallikrein excretion (corrected by body surface area) than the fullterm newborn group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally accepted that the kidney is immature at birth as expressed by the low glomerular filtration rate [12,13], by the limited capacity to reabsorb the ultrafiltered sodium [14][15][16] and by the reduced ability to concentrate urine [17], The maturation pat tern is dependent on the gestational age as evidenced by the more limited capacity of the kidney observed in preterm infants when compared with fullterm infants. Our data are consistent with previous reports by other au thors who studied the renal function in pre term and fullterm infants at similar period of life [3,17,18], Regarding kallikrein excretion, when comparing the preterm with the fullterm newborn groups, the preterm newborns had lower kallikrein excretion (corrected by body surface area) than the fullterm newborn group.…”
Section: Discussionmentioning
confidence: 99%
“…It is known of the low response of the dis tal nephron to aldosterone on the handling of sodium [15,16,19,29]. Robillard et al [6] have suggested, in addition, a low response of the immature kidney to aldosterone in regard to kallikrein production.…”
Section: Discussionmentioning
confidence: 99%
“…We chose not to induce a water diure sis with a hypotonic saline load to ensure maximal urinary dilution in our infants be cause such fluid intakes may predispose VLBW infants to development of potentially serious complications such as a persistently patent ductus arteriosus or necrotizing en terocolitis [13]. Nevertheless we found, as did Sulyok et al [2,3], mean values for abso lute urine volume and osmolar excretion in our study infants to be similar to values pre viously observed in neonates who had been volume expanded with isotonic dextran in order to inhibit vasopressin-mediated renal tubular water reabsorption [14], It would therefore seem reasonable to accept the va lidity of these indirect estimates of proximal tubular Na reabsorption in these studies.…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies have suggested that deficiencies in both proximal and distal tu bular sodium reabsorption contribute to the natriuresis [1][2][3]. The marked improvement in estimated efficiency of distal tubular func tion shown to occur during the first 2-3 weeks has been considered by many to be the major factor resulting in improved sodium conservation.…”
Section: Introductionmentioning
confidence: 99%
“…Developmental studies designed to reveal the maturation of renal sodium conservation processes have demonstrated that in lowbirth-weight premature infants the high rate of urinary sodium excretion is the result of impaired proximal and distal tubular so dium reabsorption; with advancing gesta tional and postnatal ages, a rapid improve-ment occurs in these functions, particularly in the aldosterone-mediated distal tubular sodium reabsorption [10][11][12][13],…”
Section: Introductionmentioning
confidence: 99%